L’ex-République Yougoslave de Macédoine: Entre Apaisement et Déstabilisation - Bertrand, Gilles (Études helléniques / Hellenic Studies, 1995)
As the Greek embargo continues, has the situation in the formerly Yugoslavian Macedonia calmed down or worsened since the events of autumn 1994? That Greek embargo, and the UN embargo against Serbia favour primarily the unofficial economy. The census and elections, promoted by international organizations, were to reinforce the state’s credibility. Yet, the census results were contested by the minorities due to the recent law on citizenship. The elections, boycotted by the ORIM, have confirmed the position of the team in power. It seems that these two operations haven’t eased the tension. Smuggling, Albanian and Slavo-Macedonian clandestine paramilitary groups are threatening the state’s existence, but not necessarily in the short term.